Assessment of Suicidal Youth in the Emergency Department. Issue 3 (20th October 2014) - Berk, Michele S.; Asarnow, Joan R.
<x xml:space="preserve">Abstract</x> Accurate evaluation of suicidal adolescents in the emergency department (ED) is critical for safety and linkage to follow‐up care. We examined self‐reports of 181 adolescents who presented to an ED with suicidal ideation (SI) or a suicide attempt (SA). Parents also completed self‐reports. Results showed fair agreement between parents and youth on the reason for the ED visit (e.g., SI vs. SA) and greater agreement between independent judges and youths than between judges and parents. In accordance with accepted definitions of suicide attempts (e.g., Crosby, Ortega, & Melanson, 2011; O'Carroll, Berman, Maris, Moscicki, Tanney, & Silverman, 1996, p. 237; Posner, Oquendo, Gould, Stanley, & Davies, 2007, p. 1035; Silverman, Berman, Sanddal, O'Carroll, & Joiner, 2007, p. 248), most youth with SA as the reason for the ED visit reported some intent to die associated with the attempt. Finally, youth presenting to the ED with SA did not differ clinically from youth presenting with SI, and almost half of youths with SI reported past suicide attempts. These results highlight the need to emphasize adolescents' reports in clinical decision making, suggest adolescents' defined suicide attempts similarly to published definitions, and show that assessment of past SAs, as well as present suicidal thoughts and behaviors, is critical in determining future risk.